Astragaloside IV attenuates cadmium induced nephrotoxicity in rats by activating Nrf2 - Yuchen Li; Jiayi Zhou; Tianxin Zhang; Xiaocong Li; Cheng Wu; Ziyi Zhao; Jianyuan Tang; Xiaoyu Tan; Qiongying Hu; Wenhao Liao (Scientific Reports)
Abstract Acute kidney injury (AKI) has become a disease of global concern due to its high morbidity and mortality. This has highlighted the need for renoprotective agents. Astragaloside IV (AS-IV) is a saponin isolated from Astragalus membranaceus with good antioxidant, anti-inflammatory and anti-tumor properties. In this study, HK2 cells and rat model were utilized to explore the protective effect of AS-IV against cadmium chloride-induced oxidative stress-induced apoptosis. CdCl2-induced apoptosis, ROS production, and mitochondrial membrane potential alterations were significantly inhibited in AS-IV -treated HK2 cells. Expression of the mitochondria-associated apoptotic proteins Cleaved-Caspase3, Cleaved-Caspase9, and Cleaved-PARP was significantly reduced after AS-IV intervention. In addition, AS-IV inhibited Rat weight loss and also alleviated the symptoms of CdCl2-induced nephrotoxicity in a rat model of CdCl2-induced kidney injury. Further experiments showed that AS-IV suppresses heavy metal Cd-induced mitochondria-mediated apoptosis by regulating the Nrf2/HO-1 pathway. In conclusion, AS-IV could protect the kidney from heavy metal-induced toxicity and could be used as a nephroprotective agent.